Technologies for Development: From Innovation to Social Impact - Hostettler, Silvia; Najih Besson, Samira; Bolay, Jean-Claude (Springer Nature, 2018)
Development Engineering; Technologies for Development; Innovation for Humanitarian Action; Emerging Countries; Developing Countries; Tech4Dev